Saberes da docência e práticas de ensino de História nos anos iniciais do ensino fundamental - Moura, Michele Cristina (2005)
This dissertation aims at analyzing the relationships among teachers training, knowledge and pedagogic practices in the teaching of History. We used the methodology of the thematic oral history to establish an open, sensitive, curious and polyphonic dialogue within a universe of six teachers. The narratives were documented for analysis and understanding of the following issues: How have the courses of initial training been contributing to the construction of knowledge and practices in the teaching of History? What is/are the main source(s) of the teacher s historical knowledge? How is that knowledge reconstructed and mobilized in the school daily life? How do the teachers conceive the necessary, valid and "mandatory" historical contents in the teaching/learning process of the Brazilian schools? What are the meanings and senses that the teachers attribute to the teaching of History? Besides the thematic oral interviews we analyzed some of the official documents of the institutions as follows: Projects of the undergraduate courses of Pedagogy and History of UFU; Curriculum Proposal of the "Projeto Veredas" - SEE/MG; plan notebooks; didactic materials of the schools; memorials of the teachers that take the "Projeto Veredas" course. The dissertation is divided into four chapters. In the first one we present the methodology and the subjects of the research. In the second chapter we analyze the main paradigms that orientate the processes of teachers' training in Brazil, starting in the 70s. In the third chapter we analyze the configurations, relationships and repercussions of the undergraduate courses in the teacher s training, based on the narratives and official documents. In the last chapter we register and interpret the senses and the meanings that the teachers attribute to the teaching of History. We also present a reflection on the re/constitution processes of the knowledge and practices of teaching History as well as the influences of the formal curricula, the initial/continuous training and the textbook, in the consolidation of the ways of being a teacher. The investigation revealed that knowledge and practices re/constructed in the teaching of History keep significant relationship with the teacher s daily life. We noticed that the life histories, the teacher s training and the life and work conditions of each teacher interfere directly and/or indirectly in the re/constitution of the knowledge and pedagogic practices. This research, then, expresses dimensions of the complex movement of re/construction of the knowledge and the teachers' practices besides bringing new elements for the debate concerning the teachers' training and the teaching of History.